Genetic variants in arachidonic acid pathway genes associated with NSAID-exacerbated respiratory disease. (June 2015) - Ayuso, Pedro; Plaza-Serón, María del Carmen; Blanca-López, Natalia; Doña, Inmaculada; Campo, Paloma; Canto, Gabriela; Laguna, José Julio; Bartra, Joan; Soriano-Gomis, Victor; Blanca, Miguel; Cornejo-García, José A; Perkins, James R
Aim: NSAIDs are the most frequent cause of hypersensitivity drug reactions. We have examined the association between NSAID-exacerbated respiratory disease (NERD) and genetic variants in arachidonic acid metabolism genes.Patients & methods: We included 250 NERD patients, 260 NSAID-tolerant asthmatic (NTA) subjects and 315 healthy controls.Results: Significant associations with NERD were identified for: ALOX15 rs3892408 C/C homozygous genotype (NERD vs NTA; p = 0.0001, pc = 0.0011; NERD vs controls; p = 0.0001, pc = 0.0011), PTGS-1 rs5789 A/A homozygous genotype (NERD vs NTA; p = 0.0001, pc = 0.0011; NERD vs controls; p = 0.0001, pc = 0.0011), PTGS-1 rs10306135 A/A homozygous genotype (NERD vs NTA; p = 0.0009, pc = 0.0091; NERD vs controls; p = 0.0064, pc = 0.045). Differences in ALOX5 copy number variations were also found (NERD vs NTA; p = 0.010; NERD vs controls; p = 0.0001).Conclusion: These results improve our understanding of the underlying mechanisms of NERD and may help develop a predictive test for this pathology. Original submitted 3 November 2014; Revision submitted 2 April 2015